(untitled) (Research, Society and Development, 2022)
The coronavirus disease COVID-19 has spawned the biggest public health crisis of the modern era. The sequelae that the disease imposes on many individuals brings serious consequences such as stress, anxiety and body pain. This study aims to verify if there are benefits of massage in patients who develop disorders after acquiring COVID-19. To achieve the proposed objective, descriptive research of a qualitative nature and literature review were used. The results show that through several published studies it was possible to analyze reports of patients who obtained improvements in disorders and pain after receiving body massage.